2016
DOI: 10.1007/s10311-016-0563-5
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide contamination of water by fluoride

Abstract: Fluoride contamination in water is a major problem across the globe, with health hazards such as dental and skeletal fluorosis. Most earlier studies are confined to local or regional scales. As the problem has serious socioeconomic implications, there is a need for a global perspective. Thus, here we review worldwide research for nearly a century on fluoride contamination in water. We investigated the distribution of fluoride contamination in water, its sources, mobilization and association. The major findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
102
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 341 publications
(117 citation statements)
references
References 176 publications
1
102
0
2
Order By: Relevance
“…High concentration of fluoride (> 1.5 mg/L) may lead to chronic fluoride toxicity, which manifest as dental/skeletal fluorosis, while lower concentration (< 0.8 mg/L) results in dental caries ,. Thus, the problem of excess fluoride in groundwater resources has become a burning health‐related geo‐environmental issue in various part of the globe like South Africa, China, Sri Lanka and India ,. In Indian regions, the state of Rajasthan, Gujarat, Panjab and Tamil Nadu are reported to be highly fluoride affected areas.…”
Section: Introductionmentioning
confidence: 99%
“…High concentration of fluoride (> 1.5 mg/L) may lead to chronic fluoride toxicity, which manifest as dental/skeletal fluorosis, while lower concentration (< 0.8 mg/L) results in dental caries ,. Thus, the problem of excess fluoride in groundwater resources has become a burning health‐related geo‐environmental issue in various part of the globe like South Africa, China, Sri Lanka and India ,. In Indian regions, the state of Rajasthan, Gujarat, Panjab and Tamil Nadu are reported to be highly fluoride affected areas.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 34% of groundwater samples are found under Na + -HCO 3 − or mixed type (Na + -K + -HCO 3 − ) and cause favor to fluoride dissolution in the study region. A number of previous studies suggested that the Na + -HCO 3 − water type, decreasing calcium concentration, increasing sodium concentration, and neutral-to-alkaline pH nature of water are more favorable for fluoride dissolution process, thereby accelerating the fluoride concentration in groundwater (Rao et al 2017;Ali et al 2016;Adimalla et al 2018a, b;Narsimha and Sudarshan 2017b). Moreover, Na + -HCO 3 − water type, mainly deeper groundwater, is influenced by the ion exchange process (Saxena and Ahmed 2003).…”
Section: Groundwater Typesmentioning
confidence: 99%
“…Nearly 200 million people from 25 nations are affected by the deadly disease of fluorosis (Ali et al 2016;Adimalla and Venkatayogi 2017). Fluorosis-affected regions are reported from China (Li et al , 2014Wu et al 2015), India (Narsimha and Rajitha 2018; Adimalla et al 2018a, b, c;Narsimha 2018;Sudarshan 2017a, b, 2018a, b;Rao et al 2014;Subba Rao et al 2015), Africa (Gizaw 1996), Korea (Kim and Jeong 2005), Mexico (Diaz-Barriga et al 1997), Kenya (Gikinju et al 2002) and Nigeria (Gbadebo 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibacterial effect is also limited as very little could arrive at the oral lesion area after systemic circulation [15][16][17]. Fluoride in drinking water has been used for the prevention of dental caries but might cause excessive intake, leading to fluorosis [18]. Therefore, local drug therapy is now more considered for oral infectious diseases [19,20].…”
mentioning
confidence: 99%